Fabrication and structural characterization of self-crosslinking hydrogel based on Vietnamese sources of chitosan and alginate - Tin Dai Luong; An Tran-My Le; Nhan Thien Vo; Thi Hiep Nguyen (Vietnam Journal of Science, Technology and Engineering, 2022)
Hydrogel materials have attracted extensive research over the last few decades, especially in tissue engineering, due its many comparable properties with native tissue. This study proposes a new approach to hydrogel fabrication that combines oxidized alginate (OA) into N,O-carboxymethyl chitosan (NOCC) and an oxidized hyaluronan-based hydrogel system employing low cost, domestically sourced chitosan and alginate. Hydrogel fabrication parameters including component ratio and hydrogel concentration were studied. Fourier transform infrared spectroscopy (FT-IR) analysis was applied to confirm the chemical structure of the modified materials. Fabricated hydrogel samples were assessed by cross-sectional surface morphology, equilibrium swelling degree, and in vitro degradation behaviour. The results revealed NOCC and oxidized hyaluronic acid (OHA)- OA component contributions toward hydrogel properties, a threshold of raising total polymer content within the network, and a comparison with previous formulations using unmodified alginate. Using low cost domestic resources is a promising way to reduce fabrication expenses, and further work should be performed to evaluate the potential of this cost-effective hydrogel for the tissue engineering field.